A genre analysis of promotional language in a Brahmin matrimonial website / Janet Linda a/p George Martin - George Martin, Janet Linda (2012)
This paper explores how male and female subscribers in the “Brahmins Matrimony Website” advertise themselves based on Bhatia’s promotional genre analysis moves. Generally, Indians would seek for potential life partners based of the same caste. The Brahmins are the highest caste in the Indian caste system. They are generally known to be very religious with priestly background, allowing marriages only within their own caste in order to maintain their position and also to perserve their cultural background and identity. Therefore, in this study the researcher has chosen the “Brahmins Matrimony Website” (www.brahminsmatrimony.com) as the source of data collection. There are three (3) objectives for this study. Firstly, to look at how male and female Brahmins use language to promote themselves based on Bhatia’s promotional genre analaysis moves. Secondly, to investigate how Brahmins use different aspects of their profiles such as age, occupation, and interest to advertise for potential marriage partners. Finally, the researcher also wants to investigate on Brahmins’ sense of identity in online matrimonial profiles. The data of this study is based on sixty (60) randomly selected online Brahmins Matrimony profiles that consist of thirty (30) male and thirty (30) female subscribers. The results indicate that both gender use various ways in order to describe themselves in the profiles. The findings also reveal that there are differences in the way they use language. Finally the study also shows that the Brahmins sense of identity is maintained and preserved even in this age of the internet.